KEAKTIFAN KUNJUNGAN POSYANDU DENGAN STATUS GIZI BALITA: THE ACTIVENESS OF POSYANDU VISITS AND NUTRITIONAL STATUS OF TODDLERS - Wulan Angraini; Henni Febriawati; Tresna Fatmawati; Sarkawi; Betrianita Betrianita; Riska Yanuarti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Introduction: Posyandu (Integrated Health Post) functions as a facility for health consultations and early detection of developmental disorders in toddlers, enabling prompt intervention if problems are found. Toddler compliance in attending Posyandu visits is positively associated with their nutritional status. Objective: To analyze the relationship between the frequency of Posyandu visits and the nutritional status of toddlers. Methods: This study used a quantitative approach with a cross-sectional design through observation. The study population consisted of mothers of toddlers who visited Posyandu. The sampling technique used was non-probability accidental sampling, with a total of 23 respondents. Data analysis was conducted using the chi-square test. Results: There was a significant relationship between the frequency of Posyandu visits and the nutritional status of toddlers. The more frequently toddlers attended Posyandu, the better their nutritional status. Among the respondents, 5 toddlers with infrequent visits had stunted nutritional status, while 12 toddlers with frequent visits showed normal nutritional status. Conclusion: Regular education and guidance, including home visits, are more effective in monitoring and improving toddlers’ nutritional status. toddlers.